An Evaluation of the Proficiency of Volleyball Serving Among 7th Grade Students at SMP Negeri 6 Sinjai Regency - Hasbi Asyhari; Nurliani Nurliani (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. Understanding and mastering the fundamental volleyball techniques is crucial for excelling in the sport. This comprehensive study aims to thoroughly assess the serviceability of eighth-grade students attending SMP Negeri 6 Sinjai Regency in volleyball, with a focus on evaluating their serving skills and techniques in detail. Materials and methods. The research conducted is of a quantitative descriptive nature. The survey method was utilized for data collection, specifically employing volleyball serviceability tests. The study involved a population of 136 students in the eighth grade of SMP Negeri 6 Sinjai Regency, with an accessible population of 20 individuals. The sampling method employed was Saturated Sampling, which involves sampling all members of the population, resulting in a total sample of 20 students. The research instrument utilized was a top serve ability test in volleyball. Results. In analyzing the data, we have observed that the serviceability results for volleyball games among class VIII students of SMP Negeri 6 Sinjai Regency can be categorized as follows: "Very Good" with 10% (2 students), "Good" with 25% (5 students), "Fair" with 50% (10 students), "Poor" with 15% (3 students), and "Very Poor" with 0% (0 students). Conclusion. The analysis indicates that the serviceability level in volleyball games for class VIII students at SMP Negeri 6 Sinjai Regency is primarily categorized as "Fair." The research findings can serve as valuable input for physical education teachers to enhance service abilities through suitable training methods and approaches.